Elevated levels of β C-terminal telopeptide of type 1 collagen and N-terminal mid-fragment of osteocalcin in patients with non-traumatic osteonecrosis of the femoral head - Baoxiang Zhao; Xin Sun; Zhiqun Wang; Zhi Feng; Shiying Wang (Journal of Orthopaedic Surgery and Research)
Abstract Objective To investigate the role of serum β C-terminal telopeptide of type 1 collagen (β-CTx) and N-terminal mid-fragment of osteocalcin (N-MID) concentration in non-traumatic osteonecrosis of the femoral head (NONFH). Materials and methods In this retrospective case-control study, serum β-CTx and N-MID levels were measured in 64 NONFH patients and 64 healthy controls. Propensity score matching (PSM) was used to balance the baseline characteristics of the two groups. The study was conducted at Linyi People’s Hospital between January 2023 and February 2024. The primary outcomes included the differences in serum β-CTx and N-MID levels between the two groups, their correlations with clinical parameters, and their diagnostic performance for NONFH. Results The serum concentration of β-CTx and N-MID was significantly higher in NONFH patients compared to healthy controls (β-CTx: 0.70 ± 0.30 ng/ml vs. 0.36 ± 0.16 ng/ml, P < 0.001; N-MID: 21.35 ± 8.24 ng/ml vs. 13.27 ± 3.87 ng/ml, P < 0.001). No significant differences were observed in serum β-CTx and N-MID levels among different etiological subgroups or ARCO stages. Pearson analysis revealed a positive correlation between serum β-CTx and N-MID levels, as well as β-CTx and pain duration. The ROC curve analysis showed that β-CTx had an AUC of 0.876 (95% CI 0.815–0.938) with a cut-off value of 0.505 ng/ml, sensitivity of 90.63%, and specificity of 76.56%. N-MID had an AUC of 0.860 (95% CI 0.797–0.924) with a cut-off value of 17.050 ng/ml, sensitivity of 84.38%, and specificity of 78.13%. Conclusion Serum β-CTx and N-MID levels are significantly elevated in patients with NONFH and may serve as potential biomarkers for the diagnosis of NONFH. Further studies with larger sample sizes are needed to validate these findings and explore their clinical applications.